The Hare and the Tortoise Down by the King’s Pond: A Tale of Four Translations - November, Kiat (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2007)
AbstractThis paper looks at the linguistic situation on the island of Mauritius, as revealed by the analysis of four translations of a folk-tale, originally an oral tale recounted by African slaves. The languages involved are Mauritian Creole, French and English. A brief account of the Mauritian historical and socio-linguistic development is given to contextualize my investigation. I then examine the translations from the conceptual framework of ideology, arguing that not only were they the instruments of the translators’ ideological convictions but that, in the process, they also came to symbolize the asymmetrical linguistic relations in Mauritius.